PRESERVING THE NON-PRESERVABLE GEOHERITAGE OF THE ALIAKMON RIVER: A CASE STUDY IN GEOEDUCATION LEADING TO CUTTING-EDGE SCIENCE - Rassios, A.; Grieco, G.; Batsi, A.; Myhill, R.; Ghikas, D. (Bulletin of the Geological Society of Greece, 2016)
The initial documentation of an ophiolite as oceanic lithosphere and the significance of an ophiolite’s basal sole in its emplacement were based on the research of E. Moores (1969) and J. Zimmerman (1968) at the Vourinos Ophiolite, Greece: their work became a lynch-pin in the establishment of plate tectonic theory. Key localities of their research were located along the Aliakmon River Valley between Ilariona Monastery and the village of Panayia. This same area has since been flooded (2012) with the construction of a new hydroelectric reservoir. There was no option for “saving” these sites of the birth of plate tectonic theory: what could be done to preserve their geoheritage? Between 2005 and 2008, the Institute of Geology and Mineral Exploration, with funding provided from the Public Power Corporation, sponsored geo-education to provide a “last chance” of geologic documentation of the Aliakmon Valley. In a three year period, over 60 international student and professorial-level researchers participated in the project. 37 Senior Theses were produced and 6 masters’ dissertations. The greatest achievement of the program was the revitalization of the Aliakmon data base within current, cutting-edge scientific models.